Elephant Towers at the Portals of the Pacific, Gateway to Treasure Island (H.S. Crocker Co., Inc.)
Giant Elephant Towers from the Portals of the Pacific, main gateway to the 1939 Golden Gate International Exposition on Treasure Island on San Francisco Bay